2023
DOI: 10.1002/rra.4143
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the evolution of runoff‐sediment relationship in Min River based on coupling coordination theory

Abstract: Global climate change and human activities have profoundly affected the hydrological processes in the basin. The study of the characteristics of runoff and sediment variations in the basin and their driving factors is of great significance in promoting the efficient use of water resources and high-quality development in the basin. The determination of the abrupt change point of the runoff-sediment relationship is the key to delineate the base period, and is important to assess the contribution of climate chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…They found that climate and anthropogenic factors contributed 30.20% and 69.80%, respectively, to the changes in runoff from the MRB. With runoff-sediment modeling, Wang et al [31] discovered that between 1970 and 2019, the yearly runoff from the MRB exhibited a non-significant declining trend. Climate and anthropogenic activities were identified as important drivers of runoff changes, with anthropogenic factors contributing 78.92-66.71% of the runoff changes, while climate contributed 21.08-33.29%.…”
Section: Introductionmentioning
confidence: 99%
“…They found that climate and anthropogenic factors contributed 30.20% and 69.80%, respectively, to the changes in runoff from the MRB. With runoff-sediment modeling, Wang et al [31] discovered that between 1970 and 2019, the yearly runoff from the MRB exhibited a non-significant declining trend. Climate and anthropogenic activities were identified as important drivers of runoff changes, with anthropogenic factors contributing 78.92-66.71% of the runoff changes, while climate contributed 21.08-33.29%.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the period of 1966-1993, Shao et al concluded that the average annual runoff decreased by 49.58% and the annual sediment load decreased by 77.77% in the period of 1994-2016 in the Jialing River [5]. Wang et al concluded that the annual runoff and sediment load showed a downward trend during the period of 1970-2019 in the Min River basin [6]. Berkun et al found that dams reduced water discharge by 7% and suspended sediment by 98% in the rivers located along the southeast Black Sea coast of Turkey and Georgia [7].…”
Section: Introductionmentioning
confidence: 99%